FROM THE HISTORY OF STATE–RELIGION RELATIONS IN UZBEKISTAN IN THE EARLY POSTWAR YEARS AFTER THE SECOND WORLD WAR - Adilov A. A. (TARIXIY TADQIQOTLAR, 2026)
This article is devoted to revealing the essence of the state’s religious policy carried out in the Uzbek SSR in the years following The Second World War. During this period, alongside other spheres, the religious sphere was also subjected to extensive measures of control by the central government’s highest executive bodies. At the same time, initiatives were put forward by activists in the field within the republic, and as a result, this small-scale scientific study is of particular significance in addressing such a pressing issue as identifying the root causes of the existing situation, its development, and its outcomes.